Administration in the industrial process of the cane sugar:experiences of the case of Cuban study that integrates statistical and economic methods - González, Adriana; De la Cruz, Orlando; Gómez, Bismayda; Rodríguez, Ramón (Rev. Téc. Fac. Ing. Univ. Zulia, 2015)
The necessity and importance of the continuous improvement of the industrial operations has taken sugar sector to flexible the administration tools in the industrial process of the sugarcane. This presents a high variability to use raw cane it prevails in different suppliers, and the way of operating him. In this context the present work seeks, in the first place to define the performance scenarios on the technological variables, through the statistical control and the modulation with Autoregressive Integrated of Movile Average (initials in English: ARIMA); and in second place, to quantify the variability of the process that deteriorates physical and economic indicators of the industrial acting. The main results show a remarkable improvement, for the decrease of the variability of the process that contributes to the decrease of the cost.Â